Synthesis and upconversion emission properties of Pb0·9La0·1TiO3:Yb, Tb inverse opals by sol-gel technique. (1st July 2013) - Yang, Z W; Yan, D; Song, Z G; Yu, X; Zhou, D C; Yang, Y; Yin, Z Y; Yan, L; Qiu, J B
<x xml:space="preserve">Abstract</x> Inverse opal photonic crystals of Yb3+, Tb3+ codoped Pb0·9La0·1TiO3 were synthesised by a sol-gel technique in combination with a self-assembly method. Opal template was self-assembled from suspensions of monodisperse polystyrene microspheres with a mean diameter of 400 nm via a vertical deposition process. After infiltrating the Yb3+, Tb3+ codoped Pb0·9La0·1TiO3 sol into the opal template, the polystyrene microspheres were removed by calcination at 670°C, and Yb3+, Tb3+ codoped Pb0·9La0·1TiO3 inverse opal photonic crystals were formed. The effect of photonic band gap on upconversion emissions was investigated in the Yb3+, Tb3+ codoped Pb0·9La0·1TiO3 inverse opals. Significant suppression of the upconversion emission was detected if the photonic band gap overlapped with the Tb3+ ions emission band, leading to colour tuneable upconversion photonic crystals with applications in solid state colour displays.